A cross-sectional analysis of the association between diet and insulin-like growth factor (IGF)-I, IGF-II, IGF-binding protein (IGFBP)-2, and IGFBP-3 in men in the United Kingdom - Young, N; Metcalfe, C; Gunnell, D; Rowlands, M; Lane, J; Gilbert, R; Avery, K; Davis, M; Neal, D; Hamdy, F; Donovan, J; Martin, R; et al. (2012)
Background: There is evidence of associations between insulin-like growth factor I (IGF-I), IGF-II, insulin-like binding protein-2 (IGFBP-2), IGFBP-3, and prostate cancer risk. This study examines the association between dietary factors associated with prostate cancer and serum levels of these peptides. Methods: A cross-sectional analysis of self-reported 12-month dietary intake with serum IGF and IGFBP levels was performed using data from 1,798 subjects screened negative for prostate cancer as part of a UK multicenter trial comparing treatments for this condition. Multivariable linear regression models tested associations of diet with IGFs and IGFBPs. Results: For a one standard deviation (SD) increase in dairy product and dairy protein intake, IGF-I increased by 5.28 ng/mL (95 % confidence interval: 2.64, 7.92 ng/mL) and 6.02 ng/mL (3.34, 8.71 ng/mL), respectively. A 25 % increase in calcium and selenium intake was associated with an increase in IGF-I of 5.92 ng/mL (3.77, 8.07 ng/mL) and 2.61 ng/mL (1.10, 4.13 ng/mL), respectively. A one SD increase in animal protein was associated with a decrease in IGFBP-2 of 6.20 % (-8.91, -3.41 %), and there was some evidence of an inverse association with dairy protein and calcium. There was no evidence of any dietary associations with IGFBP-3 or IGF-II. Conclusions: Diet is associated with IGF-I and IGFBP-2 levels in men in the UK, and these peptides warrant further investigation as part of randomized trials of dietary interventions to reduce the risk or progression of prostate cancer. There is no evidence that IGF-II or IGFBP-3 are mediators of dietary associations with prostate cancer. © 2012 Springer Science+Business Media B.V.